Selected aspects of psychosocial functioning of epileptics - Szpringer, Monika; Karyś, Jolanta; Karyś, Tomasz; Myszkowska, Ewa; Kosecka, Justyna; Sobczyk, Bogumił (Medical Studies/Studia Medyczne, 2014)
Introduction: Despite advances in medicine, epilepsy remains a mysterious and fearsome disease, which induces social stigma and alienation of those who suffer from it. Such attitudes are perceived by epileptics themselves, who often feel stigmatised by the sheer fact of being sick, which implies an experience of social isolation. Aim of the research: To assess the life quality of epileptic outpatients. Material and methods: The study, conducted in Q4 2013 (October-December), included 185 adult people with diagnosed epilepsy. To collect the information about the subject matter of the thesis, the authors used the method of a diagnostic survey and two questionnaires as tools – one, the authors’ own and another standardised Life Satisfaction Scale questionnaire, adopted by Z. Juczyński. Results: The obtained study results reveal that the majority of respondents consider their health condition to be poor. The satisfaction of life was higher among urban residents and those with higher education. The lowest quality of life was found among people in the 50-plus age bracket, and nearly half of respondents felt alienated due to the disease. Conclusions : A subjective assessment of satisfaction of life constitutes a significant aspect of functioning for every person. For each respondent, determination of life quality is an individual and highly complex issue. Patients who are in a similar situation from a clinical perspective may perceive their everyday limitations in a completely different way and, as a result, assess their life capabilities differently.